Learning through play: improving the reading skills through the joyful phonetics of pre-school children - Taufik, Taufik; Suminto, Suwarsi; Ibrahim, Rahimah; Abdullah, Haslinda (Bentham Science Publishers B.V, 2019)
Objective: This study examined the role of a joyful phonetic method to improve reading skills of pre-school children in Indonesia. Materials and Methods: Forty-seven pre-school children of age 4-5 years are involved in the study. Two criteria were used to select the participants of the study. Criteria included “they could not read” and “had never read”. The Solomon three groups design was used to test the effectiveness of the treatment. There were one intervention group and two control groups. One of the control groups received the treatment and another one did not. Treatment included joyful learning so that participants did not realise that they were actually learning. Results: According to data analysis, (1) joyful phonetic improved the reading skills of the experimental group more than the control group 1 and (2) the joyful phonetic improved the reading skills of the control group 2 more than the control group 1. Moreover, it was found that the phonetic, which had been given in the joyful condition, affects the improvement of the reading skills of pre-school children. Conclusion: The implication of the study is that the pre-school children would be more focused on the learning if the method has been conducted in a playing nature. Furthermore, pre-school children should be taught to read as they tend to begin their schooling.